Implicações do racismo institucional na educação básica em Cuiabá - Ribeiro, Flávia Gilene (2015)
This research aimed to identify and understand the implications of institutional racism within the framework of basic education in a school of Cuiabá. Institutional racism is unknown concept still, especially in educational institutions. In the United States in the late 1960s, it was recognized existence of adverse actions, exclusion and discrimination in some institutions, either by administrative practice or the political structures, regardless of the individual action of a racist person. Are actions and practices that produce results different for different layers of society, considering features racial. Are concepts incorporated within the system education, this knowledge is passed so informal, setting and identifying who the students 'weak' who are students "undisciplined" and what are the students who "give work" within the school. This school community, mostly black, is situated in a place non peripheral of the city, absorbed by gross weaknesses which include structural and administrative aspects. The survey sought to identify elements that institutional racism feeds within the school unit, since the Brazilian society is extremely racist. Of qualitative nature, the research used as a methodological approach some ethnography elements of empirical research as the notes in the field notebook, observation, document analysis and semi-structured interviews with 17 participants of that school community. Were research participants 9 education professionals, 4 relatives and 4 students with the purpose to analyze the implications of institutional racism within the education. Through the theoretical framework, we sought to understand the way the institutionalization of this kind of racism in Brazilian institutions and outline the research object. Data analysis indicates the presence of institutional racism fueled by interescolares mechanisms that produce the naturalization of racist practices, affecting the course of school everyday. Based on the data related to education professionals was identified that professionals are not adequately prepared to deal with racial issues in the school thus do not recognize the presence of these racist practices; in addition to highlighting the neighborhood as a negative factor in student performance; consider also the model of Human Cycle Training School as an aggravating education, since they do not understand the process and thus do not feel part. Family members do not have sufficient knowledge in the area, to understand the subtle actions of racism, nor should require them such knowledge, however, in the case of education professionals, this step should have been overcome. The students are the ones that identify the practices and evidence, once they feel on the skin such practices regularly